2012
DOI: 10.1105/tpc.111.092759
|View full text |Cite
|
Sign up to set email alerts
|

Pericentromeric Effects Shape the Patterns of Divergence, Retention, and Expression of Duplicated Genes in the Paleopolyploid Soybean  

Abstract: The evolutionary forces that govern the divergence and retention of duplicated genes in polyploids are poorly understood. In this study, we first investigated the rates of nonsynonymous substitution (Ka) and the rates of synonymous substitution (Ks) for a nearly complete set of genes in the paleopolyploid soybean (Glycine max) by comparing the orthologs between soybean and its progenitor species Glycine soja and then compared the patterns of gene divergence and expression between pericentromeric regions and ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
108
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(129 citation statements)
references
References 83 publications
(110 reference statements)
20
108
0
1
Order By: Relevance
“…We found that the densities of nonreference LTR-RTs (either gypsy or copia subclasses) detected in either the G. soja or the G. max subpopulations in pericentromeric regions were significantly higher than in chromosomal arms (Table 4), consistent with the distribution pattern of the accumulated LTR-RTs in these two types of chromatin environments in the reference genome (Du et al, 2012;Table 4, Figure 3). By contrast, the densities of the nonreference DNA TEs in both the G. max and G. soja subpopulations did not show significant differences between pericentromeric regions and chromosomal arms, although the accumulated DNA TEs were significantly enriched in pericentromeric regions compared with chromosomal arms of the reference genome (Du et al, 2012; Further comparisons between the pericentromeric regions and chromosomal arms of the 20 chromosomes revealed positive correlations between the nonreference LTR-RTs (either gypsy or copia subclasses) in either the G. max or G. soja subpopulations and the accumulated LTR-RT contents and negative correlations between the nonreference DNA TEs in either the G. max or G. soja subpopulations and the accumulated DNA TE contents (Table 5).…”
Section: Distribution Of the Nonreference Tes Versus The Accumulated supporting
confidence: 79%
See 2 more Smart Citations
“…We found that the densities of nonreference LTR-RTs (either gypsy or copia subclasses) detected in either the G. soja or the G. max subpopulations in pericentromeric regions were significantly higher than in chromosomal arms (Table 4), consistent with the distribution pattern of the accumulated LTR-RTs in these two types of chromatin environments in the reference genome (Du et al, 2012;Table 4, Figure 3). By contrast, the densities of the nonreference DNA TEs in both the G. max and G. soja subpopulations did not show significant differences between pericentromeric regions and chromosomal arms, although the accumulated DNA TEs were significantly enriched in pericentromeric regions compared with chromosomal arms of the reference genome (Du et al, 2012; Further comparisons between the pericentromeric regions and chromosomal arms of the 20 chromosomes revealed positive correlations between the nonreference LTR-RTs (either gypsy or copia subclasses) in either the G. max or G. soja subpopulations and the accumulated LTR-RT contents and negative correlations between the nonreference DNA TEs in either the G. max or G. soja subpopulations and the accumulated DNA TE contents (Table 5).…”
Section: Distribution Of the Nonreference Tes Versus The Accumulated supporting
confidence: 79%
“…By contrast, the densities of the nonreference DNA TEs in both the G. max and G. soja subpopulations did not show significant differences between pericentromeric regions and chromosomal arms, although the accumulated DNA TEs were significantly enriched in pericentromeric regions compared with chromosomal arms of the reference genome (Du et al, 2012; Further comparisons between the pericentromeric regions and chromosomal arms of the 20 chromosomes revealed positive correlations between the nonreference LTR-RTs (either gypsy or copia subclasses) in either the G. max or G. soja subpopulations and the accumulated LTR-RT contents and negative correlations between the nonreference DNA TEs in either the G. max or G. soja subpopulations and the accumulated DNA TE contents (Table 5). By contrast, negative correlations of nonreference LTR-RTs (either gypsy or copia subclasses) in either the G. max or G. soja subpopulations with gene densities and positive correlations of nonreference DNA TEs with gene densities were detected (Table 5).…”
Section: Distribution Of the Nonreference Tes Versus The Accumulated mentioning
confidence: 62%
See 1 more Smart Citation
“…Despite the widespread acceptance of these evolutionary models, with empirical examples for each (Assis and Bachtrog, 2013), more and more studies suggest that rewiring of the regulatory networks following WGD might have had a significant impact on the evolutionary consequences of duplicated genes rather than functional divergence of duplicated proteins (De Smet and Van de Peer, 2012). This proposition seems to be well supported by the observation that the majority of duplicated genes exhibit distinct patterns of expression between the two members of each pair, as revealed by genome-wide profiling of plant transcriptomes across different tissues and development stages (Danilevskaya et al, 2003;Du et al, 2012;Roulin et al, 2012).…”
Section: Introductionmentioning
confidence: 94%
“…Based on the newly annotated set of PEGs in the soybean reference genome (version 1.1, www.soybase.org) and reanalysis of the duplicated genomic blocks retained after the recent WGD event (Schmutz et al, 2010;Du et al, 2012), 16,996 singletons and 17,627 PEG pairs that correspond to 35,254 duplicates were defined (Supplemental Data Set 3). As per the assumption that a singleton is the product of deletion of one of two members of a duplicated gene pair (Schmutz et al, 2010), it is estimated that, maximally, 16,996 PEGs were eliminated after the recent soybean WGD event (Supplemental Data Set 3), suggesting rapid fragmentation of the duplicated genomes.…”
Section: Retention Of Mirna Duplicates Versus Retention Of Peg Duplicmentioning
confidence: 99%